DESIGN OF MONITORING SYSTEM FOR BANKNOTE PIGGY BANK BASED ON ANDROID - Kevin Ardiansah; Chattelin; Agfa Muhammad Prima (Indonesian Journal of Electrical Engineering and Electronics, 2025)
This research aims to design and build an Android-based banknote monitoringsystem utilizing Internet of Things (IoT) technology. This system uses TCS3200color sensor to detect the nominal value of banknotes based on RGB (Red, Green,Blue) values, NodeMCU ESP8266 as the main microcontroller, and 16x2 LCD todisplay the nominal information. The detected banknote data is sent to the Androidapplication in real-time, allowing users to monitor the balance, view the savingshistory, and control the opening and closing of the savings box through a solenoidmechanism. System testing showed a 98% success rate in detecting banknotes ofvarious denominations, displaying information on the LCD, and synchronizing datawith the Android application. This system is expected to improve children'sfinancial literacy by providing a more interactive, efficient, and safe savingsexperience.